Plan de desarrollo turístico de la comunidad rasuyacu, zona de amortiguamiento de la reserva ecológica Los Ilinizas, parroquia Toacaso, cantón Latacunga, provincia Cotopaxi - Andrango Farinango, Jorge Salvador (2013)
The idea of having a Plan of Tourist Development on the part of the community Rasuyacu Heart of Jesús, Area of Reduction of the Ecological reservation Ilinizas, is born of the necessity of to optimize the management capacity for the sustainable use of its natural and cultural resources and to strengthen the new pillars for the construction of an equal and solidary community through the tourism. Giving execution to this yearning, the first instrument technician is obtained in which the following one has been contemplated: In the first chapter the analytic diagnosis, the same one that allowed to identify the current situation in the environments economic, cultural, tourist and environmental partner at cantonal, parochial level, and mainly of the community in study, determining this way the lacks and concerning potentialities to the tourist development of the same one. In the second chapter the definition of the development areas was made identifying and evaluating its tourist attractiveness, achieving this way to settle down as the tourist main attractiveness to snowy Iliniza south. Main FODA was also elaborated by means of the active participation of the inhabitants with the purpose of identifying internal and external factors that allow to guide the programs and projects of the Plan....